2020
DOI: 10.1002/ppp.2074
|View full text |Cite
|
Sign up to set email alerts
|

Modeling thermal regime and evolution of the methane hydrate stability zone of the Yamal peninsula permafrost

Abstract: In recent years, new geophysical phenomena have been observed in the highlatitude regions of continental permafrost. Since 2014 new craters 10-20 m in diameter have been found within the Yamal Peninsula and neighboring regions. They are associated with the emissions of gases, which could have been formed during dissociation of relict gas hydrate deposits due to increases in soil temperature. This paper presents the results of numerical modeling of the thermal regime of permafrost in the north of Western Siberi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 70 publications
(147 reference statements)
0
3
0
Order By: Relevance
“…) , 𝑖𝑓 𝑃 𝑏𝑜𝑡 ≤ 𝑃 𝑠𝑎𝑡 (11) The calculated flow rate value is reintegrated at the beginning of the calculation, and the entire algorithm is iterated until the desired precision is achieved. Subsequently, the equilibrium conditions for the formation of crystalline hydrates are established utilizing the calculation methodologies shown in the referenced monographs (48,49). These methodologies are specifically tailored for application to both natural and associated petroleum gases.…”
Section: Figure 3 Nomogram For Calculating Pump Performance Parameter...mentioning
confidence: 99%
“…) , 𝑖𝑓 𝑃 𝑏𝑜𝑡 ≤ 𝑃 𝑠𝑎𝑡 (11) The calculated flow rate value is reintegrated at the beginning of the calculation, and the entire algorithm is iterated until the desired precision is achieved. Subsequently, the equilibrium conditions for the formation of crystalline hydrates are established utilizing the calculation methodologies shown in the referenced monographs (48,49). These methodologies are specifically tailored for application to both natural and associated petroleum gases.…”
Section: Figure 3 Nomogram For Calculating Pump Performance Parameter...mentioning
confidence: 99%
“…The formation of methane hydrates in the upper horizons of the permafrost zone in the past can be explained by the influence of the overlying ice sheet and marine transgression. The results of calculations with the dynamic model of thermophysical processes in the glacier-soil system showed that in the north of Western Siberia under the ice sheet [17,18], the upper boundary of the zone of stability of methane hydrates could reach the surface during the periods of glaciation at about 95-80 and 70-60 thousand years ago [19,20]. Modern warming, especially in high latitudes, accompanied by permafrost melting, increases the risk of gas emissions during the dissociation of shallow methane hydrates [20] with the formation of craters with traces of discarded rock [21,22], similar to those recorded in 2014-2020 in the permafrost zone in the north of Western Siberia.…”
Section: Introductionmentioning
confidence: 99%
“…The results of calculations with the dynamic model of thermophysical processes in the glacier-soil system showed that in the north of Western Siberia under the ice sheet [17,18], the upper boundary of the zone of stability of methane hydrates could reach the surface during the periods of glaciation at about 95-80 and 70-60 thousand years ago [19,20]. Modern warming, especially in high latitudes, accompanied by permafrost melting, increases the risk of gas emissions during the dissociation of shallow methane hydrates [20] with the formation of craters with traces of discarded rock [21,22], similar to those recorded in 2014-2020 in the permafrost zone in the north of Western Siberia. Changes in the thermal and hydrological regimes of permafrost and wetland ecosystems and associated changes in methane fluxes into the atmosphere have significant regional and global consequences [23].…”
Section: Introductionmentioning
confidence: 99%
“…The work in [34] presents the results of modeling the permafrost thickness in the north of Western Siberia (exemplified by the Yamal Peninsula) with an assessment of the methane hydrates stability zone under the influence of glaciation and subsequent sea transgression. According to the results presented, the upper boundary of the methane hydrates stability zone in Yamal could have reached the ground surface during the periods of glacial conditions.…”
Section: Introductionmentioning
confidence: 99%